2012
DOI: 10.2174/157016212802429794
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity: Do Patients Infected with HIV Practice? How Much? A Systematic Review

Abstract: Several studies have suggested that aerobic physical activity is safe and beneficial for HIV-infected adults. However, there is information lacking regarding whether HIV-infected patients practice physical activity and to what extent. Therefore, the aim of this systematic review was to determine the prevalence of physical activity, sedentary lifestyle or lack of physical activity in non-experimental conditions performed by HIV-infected subjects. The electronic search was conducted using Medline and EMBASE bibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 37 publications
3
49
1
1
Order By: Relevance
“…The use of lipidlowering therapy was low and similar among centers, but no dietary intervention had been provided, even though there is evidence of benefit equivalent to lipidlowering agents [37]. Although the frequency of physical inactivity was much higher in Recife, the effectiveness of physical activity in improving the lipid profile in HIV-infected patients in routine conditions is still unclear [38].…”
Section: Discussionmentioning
confidence: 99%
“…The use of lipidlowering therapy was low and similar among centers, but no dietary intervention had been provided, even though there is evidence of benefit equivalent to lipidlowering agents [37]. Although the frequency of physical inactivity was much higher in Recife, the effectiveness of physical activity in improving the lipid profile in HIV-infected patients in routine conditions is still unclear [38].…”
Section: Discussionmentioning
confidence: 99%
“…23 The Newcastle-Ottawa scale, 24 modified for cross-sectional studies, was applied to all the selected articles. 25,26 This scale addresses 3 domains (selection, comparability, and outcome), and the studies could be awarded 1 star for each factor in the first 2 categories (sum of 5 stars) and 2 stars for each factor in the comparability section. The sum of the stars, up to a maximum of 7, reflected the overall quality rating of each study.…”
Section: Risk Of Bias In Individual Studies and Summary Measuresmentioning
confidence: 99%
“…The physical activity levels were measured by the IPAQ; however, according to a systematic review by Schuelter-Trevisol et al 49 , physical activity levels vary according to the measurement method used. They found that HIV-positive patients showed inactivity or sedentary lifestyle percentages ranging from 19-73%.…”
Section: Tien and Grunfeldmentioning
confidence: 99%